Influence Of Tinospora Cordifolia On Wound Healing In Albino Rats - MERAVANIGE GIRISH; PRIYADARSHINI.K (International Journal of Pharma and Bio Sciences, 2012)
Objective: To investigate the effect of tinospora cordifolia (TC) on resutured incision and dead space wounds in albino rats. Materials and Methods: Resutured incision and dead space wounds were inflicted in albino rats under light ether anesthesia with aseptic precautions. Treatment group received tinospora cordifolia and control animals received vehicle orally for a period of 10 days. On the 11th day, after estimating breaking strength of resutured incision wounds, animals were sacrificed and granulation tissue removed from dead space wounds to estimate breaking strength, hydroxyproline content, quantification of granulation tissue and histopathological assessment in both control and treated groups. Results: TC significantly (P<0.05) promoted the healing process in both the wound models studied. Conclusion: TC promote wound healing, perioperative use of TC could promote the healing of surgical wounds.